AGAMA, MASYARAKAT DAN KESEJAHTERAAN SOSIAL - Cost Sahanaya; Anthonio Johan Latuihamallo (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
Sosial welfare in perpective opproximation of sociological can be see on three indicators, ie, 1), Personality, 2) Social groups and, 3). Societies. The three indicators to follow teorities can be us saw on approximation in social problems deviant behaviour (children Street) , are there, first, abolition, second, protection, and thirt, empowerment. The three approtimations is the way of acting by human to aid satisfying societies welfare, so logically by Getrude Wilson, Sosial welfare is an organized concern all people.